2013
DOI: 10.3389/fphys.2013.00138
|View full text |Cite
|
Sign up to set email alerts
|

Experimental data suggesting that inflammation mediated rat liver mitochondrial dysfunction results from secondary hypoxia rather than from direct effects of inflammatory mediators

Abstract: Systemic inflammatory response (SIR) comprises both direct effects of inflammatory mediators (IM) and indirect effects, such as secondary circulatory failure which results in tissue hypoxia (HOX). These two key components, SIR and HOX, cause multiple organ failure (MOF). Since HOX and IM occur and interact simultaneously in vivo, it is difficult to clarify their individual pathological impact. To eliminate this interaction, precision cut liver slices (PCLS) were used in this study aiming to dissect the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…For efficient reoxygenation, the mitochondrial suspension was strongly diluted in incubation buffer equilibrated with air oxygen. The iron concentration is in line with our recently published data showing in an in vitro model in the liver that 1 h hypoxia results in the release of 20 mM ferrous ions [27]. The concentrations of ferrous ions and nitrite during hypoxia were much higher than those occurring/used for treatment in vivo (Supplemental Table 1), but reached these levels after dilution during reoxygenation (Supplemental Fig.…”
Section: Experimental Setup: Mitochondrial Model Of Hypoxia/ Reoxygensupporting
confidence: 87%
See 3 more Smart Citations
“…For efficient reoxygenation, the mitochondrial suspension was strongly diluted in incubation buffer equilibrated with air oxygen. The iron concentration is in line with our recently published data showing in an in vitro model in the liver that 1 h hypoxia results in the release of 20 mM ferrous ions [27]. The concentrations of ferrous ions and nitrite during hypoxia were much higher than those occurring/used for treatment in vivo (Supplemental Table 1), but reached these levels after dilution during reoxygenation (Supplemental Fig.…”
Section: Experimental Setup: Mitochondrial Model Of Hypoxia/ Reoxygensupporting
confidence: 87%
“…30 mmol/kg tissue [45]. The data of Weidinger et al, reporting 20 mmol/kg tissue, lie in a similar range [27]. We used a high nitrite concentration, because in our model only mitochondria reduced nitrite to NO, while in the tissue this process is accelerated by Fig.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…For example, it has been shown that mitochondria dysfunction plays also an important role in developing of inflammation. Experiments using rat liver slices and isolated mitochondria demonstrated that inflammation induced by inflammatory mediators resulted in mitochondrial dysfunction due to secondary hypoxia (Weidinger et al, 2013). This study revealed hypoxiainduced attenuation of complexes I and II function in response to inflammation.…”
mentioning
confidence: 81%